MEANINGFULWORLD 30 years of Humanitarian Relief in Armenia and the Globe: Forgiveness & Meaning-making - Kalayjian, A. (Актуальная психология, 2019)
The Association of Trauma Outreach and Prevention (ATOP), Meaningfulworld, has been serving globally in 47 countries and 25 states in USA since 1988. We began immediately after the devastating earthquake in Armenia. On December 1988, a 6.8 magnitude earthquake devastated northern Armenia killing 75,000 people and leaving thousands homeless (Kalayjian, 1995; British Broadcasting Company, 2013). We began the first Mental Health Outreach Program in Armenia to assess post-traumatic symptomatology and identify factors that contributed to relief from symptoms, including meaning-making and forgiveness, and to help heal the country who was suffering. We oriented and deployed over 50 psychiatrists, psychologists, social workers, and nurses to volunteer in Armenia. Since 1988, we have had over 20 humanitarian missions in Armenia, and Karapagh.